Effect of deproteinization with calcium hypochlorite on bond strength and hybrid layer formation of universal adhesives systems to eroded dentin - Castro-Núñez, Gabriela Mariana; Alzamora-Perez, Aslhey Luz; Gavidia-Herrera, Maria Alejandra; Machaca-Apaza, Ana Lourdes; Vargas-Cotacallapa, Dannittsa Sibell; Besegato, João Felipe; Kuga, Milton Carlos [UNESP]; Escalante-Otárola, Wilfredo Gustavo (Elsevier, 2025)
Purpose: To evaluate the microtensile bond strength and hybrid layer formation of universal adhesive systems applied to eroded dentin deproteinized with calcium hypochlorite. Material and methods: Two hundred bovine teeth were sectioned, preconditioned with acid, and exposed to a 15-day acid and abrasive challenge. Specimens were divided into five groups (n = 40): deproteinization with calcium hypochlorite at 1 %, 2.5 %, and 5 % concentrations, and two controls (distilled water or 2.5 % sodium hypochlorite). Each group of 20 specimens was treated with either Solare Universal Bond or Scotchbond Universal adhesive systems and light-cured with LED. Bond strength was tested using microtensile tests. Adhesive interfaces were analyzed for failure modes and hybrid layer formation using scanning electron microscopy, and EDX analysis was used to determine elemental composition. Results: Calcium hypochlorite (1 % and 2.5 %) significantly improved bond strength with both adhesives compared to controls (p < 0.05). Solare Universal Bond showed mainly adhesive fractures, while Scotchbond Universal had more mixed fractures. The 1 % and 2.5 % calcium hypochlorite treatments enhanced hybrid layer extension with Solare Universal Bond (p < 0.05), and matched distilled water with Scotchbond Universal (p < 0.05). Sodium hypochlorite resulted in a thinner hybrid layer (p < 0.05). EDX analysis showed a decrease in Silicon with higher deproteinization concentrations. Conclusion: The bonding effects of deproteinizing eroded dentin with calcium hypochlorite depend on the concentration and adhesive system used. Deproteinization with 5 % calcium hypochlorite improved both bond strength and hybrid layer formation for Solare Universal Bond, while 1 % and 2.5 % concentrations enhanced bond strength for Scotchbond Universal without impacting hybrid layer thickness, which did not adversely affect bond strength.
Keywords: Bond strength; Calcium hypochlorite; Dentin; Sodium hypochlorite